The Perception of Lethal Risks: Evidence from a Laboratory Experiment - Manuel Schubert; Tilman Brück (Institute for the Study of Labor (IZA), 2014)
We run a novel experiment to explore the relationship between the perception of real-life risks and the demand for risk reduction. Subjects play a series of loss lotteries in which the odds are matched to the likelihood of lethal events in real life. For each risk, subjects can pay premiums in order to reduce the likelihood of total bankruptcy. Our results show a complex interplay of mortality perception and demand for risk reduction. We observe that perceived annual mortality positively affects the demand for risk reduction. Moreover, we find certain risk characteristics to affect perceived mortality, others to drive the demand for risk reduction, and some to alter both. Our findings suggest that 30 percent of all insurance payments are due to biased perceptions of annual mortality while perfect precaution could lower payments by 45 percent. Implications for risk management policies are discussed.
Keywords: C9; D81; 330; risk perception; lethal risks; experiment; insurance